Evidence flowers: An innovative, visual method of presenting "best evidence" summaries to health professional and lay audiences. (12th March 2018) - Babatunde, O.O.; Tan, V.; Jordan, J.L.; Dziedzic, K.; Chew‐Graham, C.A.; Jinks, C.; Protheroe, J.; van der Windt, D.A.
Abstract : Background & Aims: Barriers to dissemination and engagement with evidence pose a threat to implementing evidence‐based medicine. Understanding, retention, and recall can be enhanced by visual presentation of information. The aim of this exploratory research was to develop and evaluate the accessibility and acceptability of visual summaries for presenting evidence syntheses with multiple exposures or outcomes to professional and lay audiences. Methods: "Evidence flowers" were developed as a visual method of presenting data from 4 case scenarios: 2 complex evidence syntheses with multiple outcomes, Cochrane reviews, and clinical guidelines. Petals of evidence flowers were coloured according to the GRADE evidence rating system to display key findings and recommendations from the evidence summaries. Application of evidence flowers was observed during stakeholder workshops. Evaluation and feedback were conducted via questionnaires and informal interviews. Results: Feedback from stakeholders on the evidence flowers collected from workshops, questionnaires, and interviews was encouraging and helpful for refining the design of the flowers. Comments were made on the content and design of the flowers, as well as the usability and potential for displaying different types of evidence. Conclusions: Evidence flowers are a novel and visually stimulating method for presenting research evidence from evidence syntheses with multiple exposures or outcomes, Cochrane reviews, and clinical guidelines. To promote access and engagement with research evidence, evidence flowers may be used in conjunction with other evidence synthesis products, such as (lay) summaries, evidence inventories, rapid reviews, and clinical guidelines. Additional research on potential adaptations and applications of the evidence flowers may further bridge the gap between research evidence and clinical practice.